2019
DOI: 10.1177/0192513x19887524
|View full text |Cite
|
Sign up to set email alerts
|

Material and Relational Difficulties: The Impact of the Household Environment on the Emotional Well-Being of Young Black Women Living in Soweto, South Africa

Abstract: South Africa is an upper-middle income country with high levels of inequality. Young urban black women living in historically disadvantaged suburbs are particularly vulnerable to these socioeconomic inequalities. We conducted a qualitative study (four focus group discussions with young nulliparous women and 13 dual semistructured interviews between women and their mother) to better understand the household environment context of young women living in Soweto (a poor urban predominantly black township) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…These transitions challenge core values around gender norms within the households; rapidly emerging modern ideologies clash with persisting traditional cultural values (Cohen et al, 2019). On the one hand, women are perceived to comply with a patriarchal attitude to household tasks, while an emerging sociocultural drive to achieve individual emancipation is increasingly recognized among new generations of women (Cohen et al, 2019).…”
mentioning
confidence: 99%
“…These transitions challenge core values around gender norms within the households; rapidly emerging modern ideologies clash with persisting traditional cultural values (Cohen et al, 2019). On the one hand, women are perceived to comply with a patriarchal attitude to household tasks, while an emerging sociocultural drive to achieve individual emancipation is increasingly recognized among new generations of women (Cohen et al, 2019).…”
mentioning
confidence: 99%
“…Previous studies from South Africa have attributed adolescents' risky sexual behaviors to a lack of parental supervision, partly due to dysfunctional families and poor mother-daughter relationships [20]. In addition, recent studies from Soweto have shown that adolescents who do not live with both biological parents are at increased risk of adverse sexual outcomes [14]. Importantly, even with presence of both parents, some participants mentioned lack of conversations about sex, or instances where conversations were delivered in a 'warning' tone, than to constructively provide knowledge [32] and discuss choices and options [33].…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors for adolescent pregnancy include early marriage, unequal power relations and forced sexual initiation, gender-based violence, lack of skills to negotiate safer sex options [12], as well as lack of comprehensive sexuality education [13]. Poor parental supervision and single motherhood (due to parental separation) [14], unstable families, poor motherdaughter relationships, limited conversation between parents and adolescents on issues around sex [10] have also been associated with adolescent pregnancy. Sexual risk-taking behaviors, including unprotected sex, multiple sex-partners, low contraceptive use and negative peer pressure are common among young people in South Africa [15].…”
Section: Introductionmentioning
confidence: 99%
“…The trial was designed following the Standard Protocol Items (Recommendations for Interventional Trials (SPIRIT) 2013 statement). Through extensive qualitative (focus groups, in-depth individual interviews and stakeholder engagement)18–23 and epidemiological research,24–31 we identified our young women (18–28 years) as the target group given that a high proportion these women are already either overweight or obese and most will have their first child during this age range, and developed the intervention package. We initially opted for a cluster randomised study design in order to included community peer group sessions as part of the intervention.…”
Section: Methodsmentioning
confidence: 99%